The growth crisis of Germany: A blueprint of the developed economies - Norbert Berthold; Klaus Gründler (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, insbes. Wirtschaftsordnung und Sozialpolitik, 2013)
Germany has experienced tremendous growth rates in the aftermath of World War II. Since the early 1970s, growth rates declined and settled down at a more or less constant rate of 2 percent per year, only to experience a renewed negative trend around the early 2000s. We investigate the evolution of the German growth rate and particularly aim to explain the last decline. Endogenous growth theory suggest that long-run growth is mainly driven by human capital and technological progress. Our 3SLS estimations in a panel of 187 countries between 1965 and 2010 support this hypothesis. As it turns out, human capital accumulation in Germany severely lags behind the average level of the developed countries. As this may explain the moderate position of Germany in the group of the 25 richest countries, the developed countries in turn experience a period of below-average growth rates. Regardless the financial crisis from the late 2000s, growth reveals a downward trend since the turn of the millennium in nearly each of the developed economies. We argue that this decline must be traced back to a general lack of radically new ideas in the world economy. The explanation of the German growth crisis may thus be considered a blueprint of the situation in the developed economies.
Keywords: O40; O33; 330; Economic Growth; Endogenous Theory; Germany; Technical Change